Piper retrofractum Vahl. Extract, as a PPARδ and AMPK Activator, Suppresses UVB-Induced Photoaging through Mitochondrial Biogenesis and MMPs Inhibition in Human Dermal Fibroblasts and Hairless Mice. (12th February 2018) - Yun, Jungon; Kim, Changhee; Kim, Mi-Bo; Hwang, Jae-Kwan
Abstract : Photoaging occurs by UVB-irradiation and involves production of reactive oxygen species (ROS) and overexpression of matrix metalloproteinases (MMPs), leading to extracellular matrix damage. Piper retrofractum Vahl. is used as a traditional medicine for antiflatulence, expectorant, sedative, and anti-irritant; however, its antiphotoaging effect has not yet been studied. The current study investigated the antiphotoaging effect of standardized Piper retrofractum extract (PRE) on UVB-damaged human dermal fibroblasts and hairless mouse skin. PRE treatment activated the peroxisome proliferator-activated receptor delta (PPAR δ ) and the adenosine monophosphate-activated protein kinase (AMPK), consequently upregulating mitochondrial synthesis and reducing ROS production. Additionally, PRE inhibited MMPs expression via suppressing mitogen-activated protein kinase (MAPK) and activator protein-1 (AP-1). PRE downregulated UVB-induced inflammatory reactions by inhibiting the nuclear factor-kappa B (NF- κ B) activity. PRE also enhanced transforming growth factor-beta (TGF- β ) and the Smad signaling pathway, thereby promoting procollagen gene transcription. Furthermore, oral administration of PRE (300 mg/kg/day) similarly regulated the signaling pathways and increased antioxidant enzyme expression, thus attenuating physiological deformations, such as wrinkle formation and erythema response. Collectively, these results suggest that PRE acts as a potent antiphotoaging agent via PPAR δ and AMPK activation.